The Introduction Of SDN 3 Lukluk Environment Using Augmented Reality Application - Putra, Ida Bhujangga Bagus Dili; Wibawa, I Gede Arta (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020, 2020)
Every year a lot of new students enter school. To introduce new students to the school environment, the school holds an event to introduce the school environment to make them know their school environment better. However, there are still students who do not know their school environment very well. In the school environment there are many buildings with different names and to remember all of them correctly is not easy and takes a lot of time to look at all of them. To Remember all the location of the buildings and its names, it would be better if there was a application that can visualize the buildings very well. Technologies that can provide visualization and is easy to use is Augmented Reality. Augmented Reality can display the whole school environment, making it easier to see all the buildings with their names in the school environment. AR can be easily used, user only need to install AR on their smartphone device. This AR application is marker-based so that user only need to scan the marker provided with the camera and the school environment and information can be displayed.